THE EFFECT OF DIDECYLAMINE AND DI-n-DODECYL GROUP CONTAINING BORATE ESTER ADDITIVES ON FRICTION AND WEAR - Parlak, Nihat; Ozler, Latif; Gorgulu, Ahmet Orhan (Vinca Inst Nuclear Sci, 2025)
Various studies aim to reduce wear and material loss in machines where parts are in relative motion and contact. Damage caused by the wear of the material leads to work loss and financial issues. Various additives are added to oils to reduce financial losses that occur due to material wear. The widespread use and superior properties of boron minerals have drawn researchers' attention, leading to the incorporation of borate additives into oil lubricants. In this study, two different borate ester additives containing Didecylamine and Di-n-Dodecyl groups were synthesized, and their effects on wear, friction, and temperature were experimentally investigated. The additives were mixed into 10W-40 motor oil at concentrations of 0.2%, 0.6%, 1%, and 3% by weight. Experiments were conducted using a four-ball wear test device under varying speeds and contact forces. In the experiments carried out with BE1 and BE2 doped engine oil under 200 N, 400 N, and 600 N loads, it was found that the increase in the additive increased the amount of wear. In the experiments carried out with BE1 and BE2 added oils under different loads, it was observed that the increase in the additive ratio caused the contact surface and increased the amount of wear, friction coefficient, and temperature. The lowest wear amount was observed in oils with 0.2% BE2 under a 200 N load. The study concluded that adding borate ester additives to commercially available motor oils is unsuitable.
Keywords: wear; friction; borate ester; synthesizing; engine oil; oil additive